Firm’s Characteristics and Macro-Economic Variables on Expected Stock Returns - Paudel, Shiva Raj (PYC Nepal Journal of Management, 2019)
This study examines the effect of firm’s characteristics and macroeconomic variables on common stock return from the firms listed in Nepal Stock Exchange (NEPSE). The explained variable for the study is stock return which is calculated as the annual capital gain yield. The explanatory variables consist of firm size, book to market equity, earning yield, cash flow yield, GDP growth, rate of inflation, real interest rate, and money supply. The data are collected from the database of NEPSE, Nepal Rastra Bank (NRB), and the annual reports of the selected firms. The study is based on the 150 observations from the 10 sample firms for the period of 15 years (from 2003/4 to 2017/18). Fixed effect panel data analysis is used to examine the effect of firm characteristics and macroeconomic variables on common stock return in Nepalese firms. The findings confirms significant negative impact of firm size, book to market equity, earning yield, and cash flow yield on stock return in Nepalese context. Among the macroeconomic variables, GDP growth rate, and interest rate have significant negative impact on stock return. Contrarily, only the rate of inflation has significant positive impact on stock return in the context of Nepal. No significant effect of money supply is observed on common stock return in the context of Nepal.